Association of dietary total antioxidant capacity with all-cause and cardiovascular mortality in patients with chronic kidney disease: based on two retrospective cohort studies of NHANES - Yue Li; Gui-Chen Ling; Rui-Bin Ni; Shi-Hao Ni; Shu-Ning Sun; Xin Liu; Jian-Ping Deng; Xiao-Lu Ou-Yang; Jin Li; Shao-Xiang Xian; Ling-Jun Wang; Tao-Chun Ye; et al. (Renal Failure, 2023)
Background The relationship between dietary total antioxidant capacity (DTAC) and death risk among CKD populations remains unclear.Methods Based on vitamin C equivalent antioxidant capacity (VCEAC) and the component dietary antioxidant index (CDAI) indices, we analyzed two cohorts to investigate the association of DTAC with all-cause and CVD mortality in CKD patients using data from National Health and Nutrition Examination Survey (2007–2018). VCEAC (n = 6330) and CDAI (n = 6300) cohorts with mortality follow-up data available through 2018 were included. Cox models with restricted cubic splines was used to model the nonlinear association between VCEAC/CDAI and outcomes in CKD patients.Results Our results showed L-shaped associations of DTAC with all-cause mortality among individuals with CKD stages 1–2 in both cohorts. Compared to the lowest quartile, higher dietary total antioxidant intake was associated with lower all-cause mortality risks among CKD stages 1–2 after adjustment for covariates, with HRs (95%CI) of 1.00, 0.91 (0.71,1.17), 0.69 (0.53,0.90), and 0.70 (0.54,0.91) in VCEAC, and similar respective estimate trends in CDAI. After sensitivity and subgroup analyses, there were no benefits for patients with stage 3–5 CKD or albuminuria. Mediation analysis revealed that the proportions mediated in both cohorts were less consistent.Conclusions Moderate dietary total antioxidants intake has potential benefits for early-stage CKD patients. However, further evidence is needed to confirm whether patients with worsening CKD can benefit in the long term.